Structural and Magnetic Properties of Co0.5Ni0.5-xMnxFe2O4(x=0, 0.15, 0.25, 0.35, 0.5) Ferrite Nanoparticles Prepared via Sol-Gel Auto-Combustion Method - Amirabadizadeh, Ahmad; Rasouli, Mohammad; Sarhaddi, Reza (JOURNAL OF ADVANCES IN PHYSICS, 2013)
In this study, Co0.5Ni0.5-xMnxFe2O4 (x=0, 0.15, 0.25, 0.35, 0.5) ferrite nanoparticles were prepared by sol-gel auto-combustion method. Structural, magnetic and morphology properties of obtained nanoparticles were investigated with X-ray Diffraction (XRD), Vibrating Sample Magnetometer (VSM) and Transmission Electron Microscopy(TEM), respectively. The XRD results show that the most dominant peaks for samples is related to the Spinel phase. Crystalline size using Scherrer’s equation for different values of x were obtained between 44 to 64 nm. VSM results showed that the saturation magnetization and coercivity values changed with increasing Mn. TEM images obtained results are in good agreement with the XRD results.